Autologous chin graft for implant site augmentation revisited - Oliver Jacob; Manab Kosala (Wolters Kluwer Medknow Publications, 2021)
Advanced alveolar bone resorption in the maxillary anterior teeth is a common finding that limits the placement of implants for prosthetic rehabilitation. Autologous bone graft from the mandibular symphysis is one of the oldest techniques in horizontal ridge augmentation techniques for placement of implants in advanced resorption of the alveolar ridge in the maxillary anterior region. This case report revisits the technique carried out using piezoelectric osteotome for harvesting block graft from the mandible to augment the resorbed ridge horizontally to place implant in a young and healthy patient.